Pendidikan Multikultural John Dewey: Sebuah Refleksi Kritis bagi Praktik Pendidikan Agama Kristen - Simon Aponno; Aris Kusmiran Winandar; Patricia Tripani Matulessy; Ruland Metusalem Daimboa (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
This article aims to analyze John Dewey's thinking on multicultural education as well as reflect on its critical relevance to the practice of Christian Religious Education. This study uses a conceptual literature review method with a thematic analysis approach to Dewey's main work, especially Democracy and Education, which is then compared with Geneva Gay's thoughts on modern multicultural education. The results of the study show that Dewey views education as a democratic process that places experience, social interaction, and active participation as a means of forming inclusive character in a pluralistic society. Multiculturalism in Dewey's perspective is not simply an acknowledgment of differences, but a social praxis that encourages dialogue, empathy, and cross-cultural solidarity. In reflection on Christian Religious Education, Dewey's thought makes an important contribution to the development of more dialogical, humanist, and transformative learning in the midst of Indonesia's diverse reality. Christian religious education not only serves as a means of transmitting the doctrine of faith, but also as a space for the formation of students who are able to live inclusively, respect differences, and build peaceful social relations in a multicultural society.